Quran Literacy for Students with Special Needs - Hery Noer Aly; Bustomi Bustomi (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2022)
The study is aimed to investigate the implementation of teaching Quran literacy for students with disabilities. It applied qualitative. Data were collected using observation and interviews with teachers of Iqro (Quran for beginner). The participants of the study were students with disabilities studying in schools for special need in Bengkulu and Ciamis regency West Java Indonesia. The schools include MI (Madrasah Ibtidaiyyah/Islamic Elementary School) Mutiara Asyifa, Abdurrahamn Bin Auf, SDLB (Sekolah Dasar Luar Biasa/Elementary School for Special Need) Islam Amal Mulya, SLB (Sekolah Luar Biasa/School for Special Need) Baiturrahman Cisaga, and SLB Albarokah Baregbeg. The result showed that the schools have provided minimum service for teaching and learning Quran/Iqro for students with disabilities. There are two factors causing the situation; the scarcity of PAI (Pendidikan Agama Islam/Islamic Religious Education) teachers in the schools and the absence of reliable Quran reading methods. The teachers background are language teachers who had no experience and competence for Islamic religious education. In addition, the learning method for Iqro is similar to the BISINDO (Bahasa Isyarat Indonesia/Indonesian Sign Language) method for reading by sign language. This study suggests that PTKIN (State Islamic Higher Education) offering PAI to provide a program for Quran reading and writing courses for students with disabilities.